Measuring Privileged Identity in Educational Environments: Development and Validation of the Privileged Identity Exploration Scale - Watt, Sherry K.; Mueller, John A.; Parker, Eugene T.; Neel, Rebecca; Pasquesi, Kira; Kilgo, Cindy A.; Mollet, Amanda L.; Mahatmya, Duhita; , Multicultural Initiatives Consortium (Frontiers in Education, 2021)
The present study describes the development and validation of an instrument to measure defensive reactions individuals display in difficult dialogues while exploring privileged identities and interacting across difference. The increased focus on difficult dialogues when exploring privileged social identities in educational environments points to a need for the Privileged Identity Exploration Scale (PIE-S). The Privileged Identity Exploration Model (PIE) (Watt, College Student Affairs Journal., 2007, 26, 114–126; Watt et al., Counselor Education and Supervision., 2009, 49, 86–105) identifies eight defensive reactions. Using exploratory and confirmatory factor analysis, we identified and confirmed four constructs of privileged identity exploration that students exhibit when interacting across social differences, the PIE Scale (PIE-S). We provide a brief overview of the development of the PIE-S, as well as future directions for research and applications to training and facilitation in various educational settings.